Strategi dan Konsep S-T-P Program Podcast Podkesmas - Muttaqien, Muhammad; Zein, Alfandi Dafa (LUGAS Jurnal Komunikasi, 2024)
Podcasts, a rapidly evolving form of audio content distribution via the internet, are experiencing significant growth. Spotify is a frequently utilized platform for podcasts, such as Podkesmas, a content creator promoting itself as "Always funny and full of laughter". Podkesmas is strategically working to expand its listener base. Through qualitative descriptive research, the study comprehensively outlines the strategies and concepts implemented by Podkesmas to captivate its audience. The primary data collected from in-depth interviews and secondary data from documents and literature underscore Podkesmas comprehensive approach, including program planning, production and procurement, implementation, monitoring, and evaluation. Additionally, Podkesmas effectively employs the S-T-P (Strategy, Targeting, Positioning) concept to attract listeners, exemplified by its inclusion in Spotify's prestigious exclusive podcasts.